Comparative analysis of two porcine kidney decellularization methods for maintenance of functional vascular architectures. (15th July 2018) - Zambon, Joao Paulo; Ko, In Kap; Abolbashari, Mehran; Huling, Jennifer; Clouse, Cara; Kim, Tae Hyoung; Smith, Charesa; Atala, Anthony; Yoo, James J.
Graphical abstract: Abstract: Kidney transplantation is currently the only definitive solution for the treatment of end-stage renal disease (ESRD), however transplantation is severely limited by the shortage of available donor kidneys. Recent progress in whole organ engineering based on decellularization/recellularization techniques has enabled pre-clinical in vivo studies using small animal models; however, these in vivo studies have been limited to short-term assessments. We previously developed a decellularization system that effectively removes cellular components from porcine kidneys. While functional re-endothelialization on the porcine whole kidney scaffold was able to improve vascular patency, as compared to the kidney scaffold only, the duration of patency lasted only a few hours. In this study, we hypothesized that significant damage in the microvasculatures within the kidney scaffold resulted in the cessation of blood flow, and that thorough investigation is necessary to accurately evaluate the vascular integrity of the kidney scaffolds. Two decellularization protocols [sodium dodecyl sulfate (SDS) with DNase (SDS + DNase) or Triton X-100 with SDS (TRX + SDS)] were used to evaluate and optimize the levels of vascular integrity within the kidney scaffold. Results from vascular analysis studies using vascular corrosion casting and angiograms demonstrated that the TRX + SDS method was able to better maintain intact and functional microvascular architectures such as glomeruli within the acellular matrices than that by the SDS + DNase treatment. Importantly, in vitro blood perfusion of the re-endothelialized kidney construct revealed improved vascular function of the scaffold by TRX + SDS treatment compared with the SDS + DNase. Our results suggest that the optimized TRX + SDS decellularization method preserves kidney-specific microvasculatures and may contribute to long-term vascular patency following implantation. Statement of Significance: Kidney transplantation is the only curative therapy for patients with end-stage renal disease (ESRD). However, in the United States, the supply of donor kidneys meets less than one-fifth of the demand; and those patients that receive a donor kidney need life-long immunosuppressive therapy to avoid organ rejection. In the last two decades, regenerative medicine and tissue engineering have emerged as an attractive alternative to overcome these limitations. In 2013, Song et al. published the first experimental orthotopic transplantation of a bioengineering kidney in rodents. In this study, they demonstrated evidences of kidney tissue regeneration and partial function restoration. Despite these initial promising results, there are still many challenges to achieve long-term blood perfusion without graft thrombosis. In this paper, we demonstrated that perfusion of detergents through the renal artery of porcine kidneys damages the glomeruli microarchitecture as well as peritubular capillaries. Modifying dynamic parameters such as flow rate, detergent concentration, and decellularization time, we were able to establish an optimized decellularization protocol with no evidences of disruption of glomeruli microarchitecture. As a proof of concept, we recellularized the kidney scaffolds with endothelial cells and in vitro perfused whole porcine blood successfully for 24 h with no evidences of thrombosis.